Alternative Vidhi to Conversion of Cyclic CNF->GNF (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In automata theory Greibach Normal Form shows that A->aVn*, where â€˜aâ€™ is terminal symbol and Vn is nonterminal symbol where * shows zero or more rates of Vn [1]. Most popular questions, conversion of following cyclic CNF into GNF are:Question 1               S->AA | a,     A->SS | bQuestion 2               S->AB,          A->BS | b,      B->SA | aQuestion 3               S->AB,          A->BS | b,      B->AS | a      [1]To solve these questions, we need two technical lemmas and required one or more another variable like Z1. In these questions, we have cyclic nature of production called cyclic CNF. We have modified the same rule by which we get the more reliable answer with less number of productions in right hand side without using lemmas and any another variable. This above method can be applied on all problems by which we produce the GNF.